Restorative Justice Tindak Pidana “Elopement” Hukum Adat dalam Konstruksi Hukum Pidana Positif Indonesia - Sri Wahyu Kridasakti; Abd. Majid; Henny Yuningsih (Jurnal Supremasi, 2022)
This study examines the applicability of “elopement” customary law (“elopement”) in the construction of criminal law in Indonesia. This legal-system study uses a socio-legal methodology with the research locus in Mataram Marga Village, Sukadana District, East Lampung; Sade Village, Central Lombok, NTB; and Tenganan Karangasem Bali, with three findings. First, customary law (legal-culture) in determining the meaning and meaning of adult (legal and legitimate) is different from the meaning of adult according to positive law (Civil Code, Criminal Code and Law 1/1974). Second, the legal-structure of positive criminal law is superior to customary law or living-law (tradition) in the construction of restorative-justice through "elopement" legal events. Third, the norms of positive criminal law substance (legal-substance) Article 322 paragraph (1) number 2 of the Criminal Code which provides sanctions for imprisonment are more legitimate than customary law norms that provide social sanctions through traditional ceremonies. Article 322 paragraph (1) number 2 of the Criminal Code and Law 1/1974 have basically fulfilled the principles of establishing laws and regulations although they have not fully translated the principles of restorative justice. The ratio-legal restorative justice “elopement” of Indonesian customary law in the construction of the Criminal Code and Law 1/1974 is different but the legal relationship is quite harmonious. The main obstacle to the application of the principle of restorative justice in the settlement of criminal acts of "elopement" according to the construction of national law is the difficulty of mapping the standards of restorative justice benchmarks for customary law which are very diverse. Future arrangements for restorative justice "elopement" in the construction of national criminal law must follow the principle of receptio in complexio as legal politics in the regulation of national legal pluralism.